15 years of galactic surveys and hard X-ray background measurements - Krivonos Roman A.; Bird Anthony J.; Churazov Eugene M.; Tomsick John A.; Bazzano Angela; Beckmann Volker; Bélanger Guillaume; Bodaghee Arash; Chaty Sylvain; Kuulkers Erik; Lutovinov Alexander; Malizia Angela; et al. (Elsevier B.V., 2022)
The INTEGRAL hard X-ray surveys have proven to be of fundamental importance. INTEGRAL has mapped the Galactic plane with its large field of view and excellent sensitivity. Such hard X-ray snapshots of the whole Milky Way on a time scale of a year are beyond the capabilities of past and current narrow-FOV grazing incidence X-ray telescopes. By expanding the INTEGRAL X-ray survey into shorter timescales, a productive search for transient X-ray emitters was made possible. In more than fifteen years of operation, the INTEGRAL observatory has given us a sharper view of the hard X-ray sky, and provided the triggers for many follow-up campaigns from radio frequencies to gamma-rays. In addition to conducting a census of hard X-ray sources across the entire sky, INTEGRAL has carried out, through Earth occultation manoeuvres, unique observations of the large-scale cosmic X-ray background, which will without question be included in the annals of X-ray astronomy as one of the mission’s most salient contribution to our understanding of the hard X-ray sky.